A Novel Chimeric Poxvirus Encoding hNIS Is Tumor-Tropic, Imageable, and Synergistic with Radioiodine to Sustain Colon Cancer Regression - Warner, Susanne G. (Mol Ther Oncolytics, 2019)
Colon cancer has a high rate of recurrence even with good response to modern therapies. Novel curative adjuncts are needed. Oncolytic viral therapy has shown preclinical promise against colon cancer but lacks robust efficacy in clinical trials and raises regulatory concerns without real-time tracking of viral replication. Novel potent vectors are needed with adjunctive features to enhance clinical efficacy. We have thus used homologous recombination and high-throughput screening to create a novel chimeric poxvirus encoding a human sodium iodide symporter (hNIS) at a redundant tk locus. The resulting virus (CF33-hNIS) consistently expresses hNIS and demonstrates replication efficiency and immunogenic cell death in colon cancer cells in vitro. Tumor-specific CF33-hNIS efficacy against colon cancer results in tumor regression in vivo in colon cancer xenograft models. Early expression of hNIS by infected cells makes viral replication reliably imageable via positron emission tomography (PET) of I-124 uptake. The intensity of I-124 uptake mirrors viral replication and tumor regression. Finally, systemic delivery of radiotherapeutic I-131 isotope following CF33-hNIS infection of colon cancer xenografts enhances and sustains tumor regression compared with virus treatment alone in HCT116 xenografts, demonstrating synergy of oncolytic viral therapy with radioablation in vivo.